An innovative approach study Health students example - AKYURT, NURAN (E D P SCIENCES, 2017)
Globalization; A process of international integration arising from the exchange of products, ideas, cultures and worldviews. Globalization is an economic as well as political, technological and cultural process. As in other areas, technological developments have brought innovations into the training of health care workers, as well as access to information and the use of this information. These developments necessitated new orientations in the education systems of health students. In this study, the effects of computer assisted instructions involving the topics of medical and vocational terminology course on the attitudes and academic achievement levels of students' use of medical and vocational terms were investigated. Marmara University Health Services Vocational School Medical Imaging students constitute the sample of the research. In the experimental group, medical and vocational terminology topics were processed and tested by computer aided instruction method for 12 weeks.
Keywords: Computer aided teaching; Terms related to human anatomy; Cardiovascular system and endocrine system; Attitudes towards the use of medical and occupational terms; Academic achievement; MEDICAL-SCHOOLS; ANATOMY INSTRUCTION; AUGMENTED REALITY; RADIOLOGY; EDUCATION